1986
DOI: 10.1002/1097-0142(19860215)57:4<808::aid-cncr2820570421>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Primary breast cancer: Flow cytometric dna pattern in relation to clinical and histopathologic characteristics

Abstract: Cell suspensions of 59 primary operable mammary carcinomas in women were subjected to flow cytometric DNA analyses. The results were correlated to histopathological grading, clinical staging, menopausal status and estrogen receptor status. Thirty-two tumors showed a DNA peak above +25% of murine lymphocyte level and were named distinct aneuploid (AN). Twenty-seven tumors did not show such a peak and were named near diploid (ND). Low histopathological malignancy grade was associated with a high frequency of ND … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
13
0
2

Year Published

1988
1988
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(19 citation statements)
references
References 11 publications
4
13
0
2
Order By: Relevance
“…Most authors agree that DNA aneuploidy is associated with poor histological grade (Thorud et al, 1986;Moran et al, 1984;Spyratos et al, 1987;Olszewski et al, 1981;Jakobsen et al, 1984;Hedley et al, 1984;McDivitt et al, 1986;Kute et al, 1985;Kallioniemi et al, 1987;Feichter et al, 1988;Dowle et al, 1987), and the mitotic count, nuclear pleomorphism and degree of tubule formation describe much the same thing. The amount of elastin and the extent of necrosis have been associated with histological grade too (Fisher et al, 1984;Kuhajda et al, 1985).…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Most authors agree that DNA aneuploidy is associated with poor histological grade (Thorud et al, 1986;Moran et al, 1984;Spyratos et al, 1987;Olszewski et al, 1981;Jakobsen et al, 1984;Hedley et al, 1984;McDivitt et al, 1986;Kute et al, 1985;Kallioniemi et al, 1987;Feichter et al, 1988;Dowle et al, 1987), and the mitotic count, nuclear pleomorphism and degree of tubule formation describe much the same thing. The amount of elastin and the extent of necrosis have been associated with histological grade too (Fisher et al, 1984;Kuhajda et al, 1985).…”
Section: Discussionsupporting
confidence: 65%
“…The occurrence of aneuploidy in histological subtypes of breast cancer has received scant attention; only mucinous carcinomas have been extensively studied (Toikkanen et al, 1988). The percentage of non-diploid tumours was high in medullary (86%) and ductogenic NOS (74%) carcinomas, and low in lobular (43%) and tubular (40%) carcinomas (Table II).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have shown correlations between cellular DNA content, as measured by flow cytometry, and other pretreatment factors (Moran et al, 1984;Kute et al, 1985;Thorud et al, 1986;Dressler et al, 1988;Feichter et al, 1988). Fewer have examined the relationship between the results of flow-cytometric DNA analysis, in particular Sphase fraction, and clinical course.…”
mentioning
confidence: 99%